E-Sampah Sebagai Salah Satu Wujud Smart Village; Study Analisa dan Perancangan - Saffana Assani’; Hermanto Hermanto (ikraith-informatika, 2021)
A waste bank is a place for collecting waste which can then be exchanged for money orbasic necessities. In managing transactions at the waste bank, they still use the manual methodby recording every waste exchange using a ballpoint pen, the waste bank customer's savingsbook, and a large notebook for the admin. The manual method causes several problems thatoften occur, including; lost the waste bank passbook, lost the admin notebook, needed a place tostore recording tools, and miswritten or miscalculated during transactions at the waste bank. Inorder to overcome these problems, this study aims to make analysis and design for an applicationthat can be used to help manage data management in waste banks. It is also the first step for avillage to become a smart village. The application that will be developed is the e-samahapplication.This research uses an extreme programming methodology, functional and non-functionalanalysis, system design using UML (unified modeling language), database design using CDM(conceptual data model) and PDM (physical data model), and is planned for development usingboostrap and codeigniter. . For now, the research results are in the form of analysis and designdocuments which can later be used as a reference in application development.